2008
DOI: 10.1038/bjp.2008.267
|View full text |Cite
|
Sign up to set email alerts
|

Predicting QT prolongation in humans during early drug development using hERG inhibition and an anaesthetized guinea‐pig model

Abstract: Background and purpose: Drug-induced prolongation of the QT interval can lead to torsade de pointes, a life-threatening ventricular arrhythmia. Finding appropriate assays from among the plethora of options available to predict reliably this serious adverse effect in humans remains a challenging issue for the discovery and development of drugs. The purpose of the present study was to develop and verify a reliable and relatively simple approach for assessing, during preclinical development, the propensity of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 39 publications
1
64
1
Order By: Relevance
“…Alternatively, Gintant et al have shown that a hERG safety margin of 45-fold between the IC 50 dose and the free plasma drug concentration predicts the absence of a QT effect >5 ms with a sensitivity of 64% and a specificity of 88%, highlighting the relative weakness of this assay for truly predicting QTc prolongation clinically [18]. Interpretation of these results is further complicated by the lack of standards for the hERG patch clamp assay and the associated variability of results observed between different laboratories which may be as high as a 20-fold difference in IC 50 values for a specific drug [19]. Further contributing to this weakness is that hERG current block is influenced by the type of mammalian cell line employed, the temperature of the experimental preparation, the configuration of the potassium channel which may be open or closed during testing, and the stimulation frequency and protocol used [20].…”
Section: Limitations Of the Tqt And Herg Centric Worldmentioning
confidence: 99%
“…Alternatively, Gintant et al have shown that a hERG safety margin of 45-fold between the IC 50 dose and the free plasma drug concentration predicts the absence of a QT effect >5 ms with a sensitivity of 64% and a specificity of 88%, highlighting the relative weakness of this assay for truly predicting QTc prolongation clinically [18]. Interpretation of these results is further complicated by the lack of standards for the hERG patch clamp assay and the associated variability of results observed between different laboratories which may be as high as a 20-fold difference in IC 50 values for a specific drug [19]. Further contributing to this weakness is that hERG current block is influenced by the type of mammalian cell line employed, the temperature of the experimental preparation, the configuration of the potassium channel which may be open or closed during testing, and the stimulation frequency and protocol used [20].…”
Section: Limitations Of the Tqt And Herg Centric Worldmentioning
confidence: 99%
“…[7] Moreover, numerous ligand-based QSAR models for predicting hERG inhibition have been developed, many of which are reviewed in recent articles by Thai et al [8,9] Both regression models, designed to directly predict hERG IC 50 values, i.e. the half-maximal inhibitory concentration, [5] typically giving 50 % channel blockade in electrophysiological assays, [10,11] and classification models have been developed. Here, our focus is on classification models.…”
Section: Computational Approachesmentioning
confidence: 99%
“…Similarly, Yao et al [11] proposed a safety margin of 300 : 1 (hERG IC 50 : maximum unbound plasma concentration) to separate drugs causing QT interval prolongation and TdP and those inducing neither cardiac disorder.…”
Section: Toxicologically Relevant Potency Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the ionic mechanisms of repolarization in adult rats and mice differ from larger species including humans, so that use of these species is not considered appropriate. Although there is clear preference for safety pharmacology studies to be performed in conscious free-moving animals in the ICH S7A guideline, anesthetized (e.g., isoflurane or halothane) animals such as dogs and guinea pigs are generally regarded as more useful because of higher sensitive to drug-induced QT prolongation than conscious animals, and better control of the heart rate (e.g., through cardiac pacing at a constant rate) (Tashibu et al, 2005;Yao et al, 2008).…”
Section: Potential Pre-clinical Approach For Qt Risk Assessmentmentioning
confidence: 99%